Nano-whisker reinforced silicon nitride combined silicon carbide ceramic and preparation method thereof
By in situ generating nanowhiskers in silicon nitride combined with silicon carbide ceramics, combined with direct nitriding method and reaction seepage method, the problem of excessive brittleness of traditional ceramic materials is solved, and the toughening and preparation efficiency of the material are improved.
Patent Information
- Application Number
- CN202411964453.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional silicon nitride combined with silicon carbide ceramic materials have problems such as excessive brittleness and low toughness, which leads to brittle fractures that are prone to occur during application, limiting their performance.
Nanowhiskers are generated in situ in silicon nitride-combined silicon carbide ceramics, and a one-step nitriding reaction sintering method combined with direct nitriding method and reactive smelting method are enhanced.
The good toughening effect of silicon nitride combined with silicon carbide ceramics is achieved, the material preparation efficiency is improved, and the preparation process of ceramic materials is simplified.
Smart Images

Figure CN119751104A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nano whisker reinforced silicon nitride bonded silicon carbide ceramic and a preparation method thereof, belonging to the technical field of preparation of silicon nitride bonded silicon carbide ceramics. Background Art
[0002] Silicon nitride (Si3N4) and silicon carbide (SiC) are both compounds with extremely strong covalent bonds and have similar physical and chemical properties. Silicon nitride combined with silicon carbide ceramic products made by combining the advantages of the two have a series of excellent properties such as high temperature resistance, corrosion resistance, wear resistance, erosion resistance, and oxidation resistance; as a high-grade refractory material, its normal operating temperature in various atmospheres can reach about 1500℃, so it is widely used in ceramics, non-ferrous metallurgy, steel metallurgy, powder metallurgy, chemical industry and other industries.
[0003] However, traditional silicon nitride bonded silicon carbide ceramics have the common problems of excessive brittleness and low toughness. Brittle fracture is prone to occur during application, causing material damage, and their application is limited to a certain extent. At present, the main solutions to this defect include: introducing nano whiskers or fibers into silicon nitride bonded silicon carbide ceramics to toughen them, and achieving energy loss of internal stress in ceramic materials through mechanisms such as fiber breakage, fiber debonding, fiber pull-out, crack bridging and crack deflection, which can improve the toughness of the bonded ceramic materials. However, some of the externally added whisker reinforcements are not easy to disperse and are easily mechanically damaged during the dispersion process, resulting in defects in the bonded ceramic material, which has a certain impact on its performance. Summary of the invention
[0004] In order to overcome the defects of the prior art, the purpose of the present invention is to provide a nano-whisker reinforced silicon nitride bonded silicon carbide ceramic and a preparation method thereof. Through the simple preparation process of the present invention, nano-whiskers can be generated in situ to achieve good toughening of silicon nitride bonded silicon carbide ceramics, which is beneficial to application.
[0005] The present invention provides a method for preparing nano whisker reinforced silicon nitride bonded silicon carbide ceramics, comprising the following steps:
[0006] 1) By mass fraction, 55-75% silicon carbide powder, 15-35% silicon powder and 10-20% carbon black are used as main raw materials, mixed with a binder, a dispersant and water to prepare a ceramic slurry;
[0007] 2) pouring the ceramic slurry into a mold, standing and drying it to form a porous ceramic body, and demolding it to obtain a porous ceramic body;
[0008] 3) The porous ceramic body is buried with silicon powder twice the mass of the porous ceramic body, and the temperature is raised to 1200-1500°C and kept in a flowing nitrogen atmosphere, and Si3N is obtained by direct nitridation of the silicon powder.4nw / SiC / C porous ceramic preform; then heating to 1600-1700°C, vacuum insulation under vacuum conditions of 1-30Pa, and then cooling to obtain nano whisker reinforced silicon nitride combined with silicon carbide ceramics.
[0009] In the silicon nitride bonded silicon carbide ceramic preparation technology provided by the present invention, Si3N4 ceramic nano whiskers are generated in situ in a porous ceramic body by direct nitridation of silicon powder, and then molten Si reacts with carbon black to generate SiC by reactive infiltration to achieve reactive sintering of the ceramic material. The present invention mainly uses a one-step nitridation reaction sintering method that combines a direct nitridation method with a reactive infiltration method to prepare nano whisker-reinforced silicon nitride bonded silicon carbide ceramics, thereby improving the material preparation efficiency, and through the stress loss mechanism of the in-situ generated nano whiskers inside the material, the toughening of the silicon nitride bonded silicon carbide ceramics is achieved.
[0010] The first step of the method described in the embodiment of the present invention is to prepare a ceramic slurry, wherein 55-75wt% of silicon carbide powder, 15-35wt% of silicon powder and 10-20wt% of carbon black are used as main raw materials, and a binder and a dispersant are added and mixed with water to obtain the ceramic slurry.
[0011] In the step 1), the purity of the silicon powder in the main raw material is greater than or equal to 90%, specifically 90-99.9%; its particle size is 1-10 μm. In some embodiments, the purity of the silicon carbide powder is greater than 85%, specifically 85-99.9%, and the particle size is 5-40 μm. The purity of the carbon black is greater than 95%, specifically 95-99.9%, and the particle size is 1-20 μm.
[0012] In the step 1), according to the mass fraction ratio, preferably, silicon carbide powder with a particle size of 5 to 40 μm, carbon black with a particle size of 1 to 20 μm and silicon powder with a particle size of 1 to 10 μm are ball-milled and mixed, such as ball-milling for 3 hours to fully mix them, to obtain a ball-milled raw material. Wherein, the mass fraction of the silicon carbide powder can be 55%, 60%, 65%, 70%, 75%, the mass fraction of the silicon powder can be 15%, 20%, 30%, 35%, and the carbon black can be 10%, 15%, 16%, 20%, etc.
[0013] In the step 1), preferably, 1-5% of the total mass of a binder and 1-5% of the total mass of a dispersant are added to the main raw material, and then 80-100% of the total mass of water is added thereto, stirred and mixed, to prepare a ceramic slurry.
[0014] Preferably, in step 1), the binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose, further hydroxymethyl cellulose sodium or hydroxyethyl cellulose. Moreover, the amount of the binder can be 2-5wt% of the total mass of the main raw material.
[0015] In the step 1), the dispersant is preferably one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester, more preferably ethanol, methylpentanol or polyethylene glycol; and the amount thereof can be 3-5wt% of the total mass of the main raw material. The main raw material of the powder, the binder, the dispersant, etc. in the embodiment of the present invention can be conventional commercial products, and the water used is usually deionized water.
[0016] The second step of the method described in the embodiment of the present invention is to prepare a porous ceramic body by pouring the ceramic slurry into a mold, allowing it to stand and dry to form, and then demolding the body.
[0017] Preferably, the step 2) comprises: pouring the ceramic slurry into a mold, leaving it to stand for 7 to 9 hours (such as 8 hours, 8.5 hours), freeze-drying or forced air drying for 24 hours, and demolding to obtain a porous ceramic body.
[0018] After obtaining the porous ceramic body, the embodiment of the present invention uses silicon powder twice as much as the porous ceramic body to bury the porous ceramic body, heats up to 1200-1500° C. in a flowing nitrogen atmosphere and keeps the temperature, and directly nitrides the silicon powder to obtain Si3N 4nw / SiC / C porous ceramic preform; then heating to 1600-1700°C, vacuum insulation under vacuum conditions of 1-30Pa, and then cooling to obtain nano whisker reinforced silicon nitride combined with silicon carbide ceramics.
[0019] The step 3) of burying the porous ceramic body comprises: weighing silicon powder of the same mass as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing silicon powder of the same mass and spreading it on the porous ceramic body so that it is buried in the silicon powder. The purity and particle size range of the silicon powder used here can be the same as those described above.
[0020] In the embodiment of the present invention, the graphite crucible can be placed in a vacuum carbon tube furnace, the air inlet valve and the exhaust valve are opened, the temperature is raised to 1250-1450° C. in a flowing nitrogen atmosphere, and the temperature is kept to perform nitridation to form Si3N 4nw / SiC / C porous ceramic preform. In the embodiment of the present invention, Si3N4 ceramic nano whiskers are in-situ generated in the porous ceramic preform mainly by direct nitridation of silicon powder.
[0021] In an embodiment of the present invention, after the insulation is completed, the air inlet valve and the exhaust valve are closed, the vacuum valve and the vacuum pump are opened, and the vacuum degree in the carbon tube furnace is preferably maintained at 5-20Pa, the temperature is raised to 1600-1700°C and kept warm for a certain period of time; after the vacuum insulation is completed, it can be naturally cooled to obtain a nano-whisker reinforced silicon nitride bonded silicon carbide ceramic material.
[0022] In the step 3), the heat preservation time in the nitrogen atmosphere is 2 to 10 hours, preferably 2 to 6 hours; the vacuum heat preservation time is 30 to 120 minutes, preferably 30 to 60 minutes. After nitridation, the embodiment of the present invention uses reactive infiltration (vacuum reactive infiltration temperature is 1600 to 1700° C.) to react molten Si with carbon black to generate SiC, thereby achieving reactive sintering of enhanced bonding ceramic materials.
[0023] The invention provides nano whisker reinforced silicon nitride combined with silicon carbide ceramics prepared by the above-mentioned preparation method, which has Si3N4 ceramic nano whiskers.
[0024] Compared with the prior art, the present invention provides a preparation technology for bonded silicon carbide ceramics with a simple process and easy-to-control process. In the preparation method described in the present invention, Si3N4 ceramic nanowhiskers are generated in situ in a porous ceramic body by direct nitridation of silicon powder, and then molten Si and carbon black are reacted by reactive infiltration to generate SiC to achieve reactive sintering of the ceramic material; that is, a one-step nitridation reaction sintering method combining direct nitridation and reactive infiltration is used to obtain a nanowhisker-reinforced silicon nitride bonded silicon carbide ceramic material. The present invention mainly achieves a good toughening effect on silicon nitride bonded silicon carbide ceramics through the stress loss mechanism of in-situ generated nanowhiskers inside the material, simplifies the preparation process of the ceramic material, and has high preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention or the core of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings under the premise of continuous creative work.
[0026] Figure 1 Si3N prepared for the present invention 4nw / SiC / C porous ceramic preform XRD pattern;
[0027] Figure 2 Si3N prepared for the present invention 4nw SEM image of / SiC / C porous ceramic preform. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0029] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0030] Unless otherwise specified, all reagents and raw materials used in the present invention are commodities that can be purchased from the market or products that can be prepared by recognized methods, and material sample testing is carried out in accordance with national standard methods.
[0031] Example 1
[0032] The steps of nano whisker reinforced silicon nitride bonded silicon carbide ceramic and preparation method thereof include:
[0033] Step 1: With 60wt% of silicon carbide powder, 30wt% of silicon powder and 10wt% of carbon black as the main raw materials, the silicon carbide powder, silicon powder and carbon black are ball-milled for 3h to be fully mixed, the ball-milled raw materials are placed in a stirring tank, 5wt% of the total weight of the main raw materials, a binder and 5wt% of the total weight of the main raw materials are added, and then 100% of the total weight of the main raw materials is added. Deionized water is added, and stirring is continued for 45min to obtain a ceramic slurry;
[0034] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, and then demould it after forced air drying for 24 hours to obtain a porous ceramic body;
[0035] Step 3, weighing the same weight of silicon powder as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder, placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1250° C. in a flowing nitrogen atmosphere, and keeping it warm for 3 hours;
[0036] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 5Pa, heat to 1600°C, and keep warm for 30 minutes. After the insulation is completed, cool naturally to obtain nano-whisker reinforced silicon nitride bonded silicon carbide ceramic material.
[0037] The purity of the silicon carbide powder is 95% and the particle size is 5μm; the purity of the silicon powder is 99% and the particle size is 5μm; the purity of the carbon black is 98% and the particle size is 15μm. The binder is sodium hydroxymethyl cellulose and the dispersant is polyethylene glycol. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 352MPa and the fracture toughness is 4.3MPa·m 1 / 2 .
[0038] Example 2
[0039] The same as Example 1, the only difference is that the nitriding temperature is 1300° C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 346 MPa, and the fracture toughness is 4.1 MPa·m 1 / 2 .
[0040] Example 3
[0041] The same as Example 1, the only difference is that the vacuum reaction infiltration temperature is 1650°C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 338MPa, and the fracture toughness is 4.5MPa·m 1 / 2 .
[0042] Example 4
[0043] Step 1: Using 65wt% of silicon carbide powder, 20wt% of silicon powder and 15wt% of carbon black as main raw materials, ball-mill the silicon carbide powder, silicon powder and carbon black for 3h to fully mix them, put the ball-milled raw materials into a stirring tank, add 2wt% of the total weight of the main raw materials as a binder and 4wt% of the total weight of the main raw materials as a dispersant, then add 80% of the total weight of the main raw materials as deionized water, continue stirring for 60min, and obtain a ceramic slurry;
[0044] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, and then demould it after forced air drying for 24 hours to obtain a porous ceramic body;
[0045] Step 3, weighing the same weight of silicon powder as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder, placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1300° C. in a flowing nitrogen atmosphere, and keeping it warm for 2 to 10 hours;
[0046] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 20Pa, heat up to 1650°C, and keep warm for 60 minutes. After the insulation is completed, cool naturally to obtain nano-whisker reinforced silicon nitride bonded silicon carbide ceramic material.
[0047] The purity of the silicon carbide powder is 99% and the particle size is 40μm; the purity of the silicon powder is 96% and the particle size is 3μm; the purity of the carbon black is 99% and the particle size is 20μm. The binder is hydroxyethyl cellulose and the dispersant is methyl amyl alcohol. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 348MPa and the fracture toughness is 4.1MPa·m 1 / 2 .
[0048] Example 5
[0049] The same as Example 4, the only difference is that the vacuum reaction infiltration temperature is 1600°C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 352MPa, and the fracture toughness is 4.0MPa·m 1 / 2 .
[0050] Example 6
[0051] The same as Example 4, the only difference is that the nitriding temperature is 1400° C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 343 MPa, and the fracture toughness is 4.7 MPa·m 1 / 2 .
[0052] Example 7
[0053] Step 1: With 55wt% of silicon carbide powder, 30wt% of silicon powder and 15wt% of carbon black as the main raw materials, the silicon carbide powder, silicon powder and carbon black are ball-milled for 3h to be fully mixed, the ball-milled raw materials are placed in a stirring tank, 5wt% of the total weight of the main raw materials as a binder and 5wt% of the total weight of the main raw materials as a dispersant are added, and then 80% of the total weight of the main raw materials as deionized water are added thereto, and stirring is continued for 30min to obtain a ceramic slurry;
[0054] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, and then demould after forced air drying for 24 hours to obtain a porous ceramic body;
[0055] Step 3, weighing the same weight of silicon powder as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder, placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1400° C. in a flowing nitrogen atmosphere, and keeping it warm for 2 hours;
[0056] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 15Pa, heat to 1600°C, and keep warm for 60 minutes. After the insulation is completed, cool naturally to obtain nano-whisker reinforced silicon nitride bonded silicon carbide ceramic material.
[0057] The purity of the silicon carbide powder is 97% and the particle size is 20μm. The purity of the silicon powder is 98% and the particle size is 4μm. The purity of the carbon black is 99% and the particle size is 10μm. The binder is hydroxyethyl cellulose and the dispersant is ethanol. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 372MPa and the fracture toughness is 4.8MPa·m 1 / 2 .
[0058] Example 8
[0059] The same as Example 7, the only difference is that the nitriding temperature is 1350° C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 366 MPa, and the fracture toughness is 4.5 MPa·m 1 / 2 .
[0060] Example 9
[0061] The same as Example 7, the only difference is that the vacuum reaction infiltration temperature is 1700°C. The bending strength of the nano whisker reinforced silicon nitride bonded silicon carbide ceramic is 378MPa, and the fracture toughness is 4.7MPa·m 1 / 2 .
[0062] Figure 1 Before the implementation of the present invention, the Si3N prepared by direct nitridation at 1400°C was explored. 4nw / SiC / C porous ceramic preform XRD (X-ray diffraction) diagram, analysis shows that Si is nitrided to Si3N4 and a small amount of C remains, which can be used as a carbon source for vacuum reactive infiltration.
[0063] Figure 2 Before the implementation of the present invention, the Si3N prepared by direct nitridation at 1400°C was explored. 4nw / SiC / C porous ceramic preform SEM (scanning electron microscope) image, analysis shows that Si3N4 whiskers are generated in situ in the porous ceramic preform, and have no effect on the SiC and C grains and the pore distribution of the porous ceramic, so the subsequent vacuum reaction infiltration treatment can be carried out normally.
[0064] It can be seen from the above embodiments that the embodiment of the present invention uses a one-step method combining direct nitridation of silicon powder in a nitrogen atmosphere with reactive infiltration to prepare a Si3N4 nanowhisker-reinforced silicon nitride-bonded silicon carbide ceramic material. The process of the present invention is simple and easy to control, which improves the efficiency of material preparation; and it effectively achieves toughening of silicon nitride-bonded silicon carbide ceramic materials through the stress loss mechanism of in-situ generated Si3N4 nanowhiskers inside the material.
[0065] It should be noted that, for those skilled in the art, several improvements and modifications may be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing nano whisker reinforced silicon nitride bonded silicon carbide ceramics, characterized in that: The steps include: 1) By mass fraction, 55-75% silicon carbide powder, 15-35% silicon powder and 10-20% carbon black are used as main raw materials, mixed with a binder, a dispersant and water to prepare a ceramic slurry; 2) pouring the ceramic slurry into a mold, standing and drying it to form a porous ceramic body, and demolding it to obtain a porous ceramic body; 3) The porous ceramic body is buried with silicon powder twice the mass of the porous ceramic body, and the temperature is raised to 1200-1500°C and kept in a flowing nitrogen atmosphere, and Si3N is obtained by direct nitridation of the silicon powder. 4nw / SiC / C porous ceramic preform; then heating to 1600-1700°C, vacuum insulation under vacuum conditions of 1-30Pa, and then cooling to obtain nano whisker reinforced silicon nitride combined with silicon carbide ceramics.
2. The preparation method according to claim 1, characterized in that: In the step 1), the purity of the silicon powder in the main raw material is greater than or equal to 90%, and the particle size is 1 to 10 μm.
3. The preparation method according to claim 2, characterized in that: In the step 1), silicon carbide powder with a particle size of 5 to 40 μm, carbon black with a particle size of 1 to 20 μm and silicon powder are ball-milled and mixed according to the mass fraction ratio to obtain a ball-milled raw material.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 1), 1-5% of the total mass of a binder and 1-5% of the total mass of a dispersant are added to the main raw material, and then 80-100% of the total mass of water is added thereto, and the mixture is stirred and mixed to prepare a ceramic slurry.
5. The preparation method according to claim 4, characterized in that: In the step 1), the binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose.
6. The preparation method according to claim 4, characterized in that: In the step 1), the dispersant is one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester.
7. The preparation method according to any one of claims 1 to 3, characterized in that: The step 2) comprises: pouring the ceramic slurry into a mold, leaving it to stand for 7 to 9 hours, freeze-drying or blast drying it for 24 hours, and demolding to obtain a porous ceramic body.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The step 3) of burying the porous ceramic body comprises: weighing silicon powder of the same mass as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing silicon powder of the same mass and spreading it on the porous ceramic body to bury it in the silicon powder.
9. The preparation method according to claim 8, characterized in that: In the step 3), the heat preservation time under the nitrogen atmosphere is 2 to 10 hours; the heat preservation time under the vacuum atmosphere is 30 to 120 minutes.
10. The nano-whisker reinforced silicon nitride bonded silicon carbide ceramic prepared by the preparation method according to any one of claims 1 to 9, comprising Si3N4 ceramic nano-whiskers.
Citation Information
Patent Citations
Method of sintering high-toughness silicon carbide ceramic by using vacuum reaction
CN105367058A
Silicon nitride nanowire reinforced porous silicon carbide material and preparation method thereof
CN106747640A
High-strength high-toughness ceramic composite material and preparation method thereof
CN112645713A
Preparation method of silicon carbide ceramic and silicon carbide ceramic material prepared by preparation method
CN116023148A
Silicon nitride whisker reinforced silicon carbide / polymer composite material and preparation method thereof
CN116355353A
Cited By
Synergistic reinforced silicon nitride composite ceramic as well as preparation method and application thereof
CN120365080A